Duration of Inflammatory Bowel Disease Is Associated With Increased Risk of Cholangiocarcinoma in Patients With Primary Sclerosing Cholangitis and IBD. (May 2016) - Gulamhusein, Aliya F; Eaton, John E; Tabibian, James H; Atkinson, Elizabeth J; Juran, Brian D; Lazaridis, Konstantinos N
Abstract : OBJECTIVES: Primary sclerosing cholangitis (PSC) often coexists with inflammatory bowel disease (IBD) and can be complicated by cholangiocarcinoma (CCA), a lethal malignancy for which reliable predictors remain unknown. We aimed to characterize the influence of colectomy and IBD duration on risk of CCA in patients with PSC‐IBD. METHODS: A retrospective review of patients with PSC‐IBD seen at the Mayo Clinic, Rochester, between January 2005 and May 2013 was performed. The primary outcome was time to development of CCA and our goal was to determine whether the risk differed between patients with and without colectomy. Risk factors were assessed using univariable and multivariable Cox proportional hazard models where colectomy, IBD disease duration, and development of advanced liver disease were treated as time‐dependent covariates. RESULTS: A total of 399 patients with PSC‐IBD were included in the study, of whom 137 had a colectomy and 123 patients developed CCA. Age‐adjusted univariate Cox proportional hazard models demonstrated that colectomy (hazard ratio (HR) 1.53, 95% confidence interval (CI) 1.05–2.22, P =0.02) and duration of IBD (HR 1.37, 95% CI 1.15–1.63, P <0.01) were associated with an increased risk of CCA, and colonic neoplasia (HR 1.52, 95% CI 0.97–2.37, P =0.06) and colectomy for colonic neoplasia (HR 1.62, 95% CI 1.01–2.61, P =0.05) approached significance. Among patients with a history of colectomy, colonic neoplasia as the indication for surgery was associated with a particularly increased risk of CCA (HR 2.91, 95% CI 1.24–6.84, P =0.01) compared with medically refractory disease. On multivariate analysis, duration of IBD remained significantly associated with CCA (HR 1.33, 95% CI 1.11–1.60, P <0.01). The influence of IBD duration on CCA risk was not modified after colectomy ( P =0.69). CONCLUSIONS: Prolonged duration of IBD is associated with an increased risk of CCA in patients with PSC‐IBD, and colectomy itself does not modify this risk. These findings identify a subset of patients who are at high risk of this lethal complication and in need of close surveillance.